A New Projection Algorithm for Generalized Variational Inequality. (24th January 2010) - Fang, Changjie; He, Yiran
Abstract : We propose a new projection algorithm for generalized variational inequality with multivalued mapping. Our method is proven to be globally convergent to a solution of the variational inequality problem, provided that the multivalued mapping is continuous and pseudomonotone with nonempty compact convex values. Preliminary computational experience is also reported.